Physicochemical properties of local fruits extract as antimicrobial agents and stain remover. - Nur Ain Abd Aziz (2014)
The aim of this study was to evaluate the physicochemical properties of fifteen local fruit types and measure the antimicrobial properties and stain remover abilities at three maturity fruit stages (young, mature, ripe). Fifteen local fruit types were analysed for their physicochemical properties included total soluble solids (TSS), titratable acidity (TA) and pH at different maturity stages. The potential local fruits, particularly sour taste was selected for quantification of organic acid (oxalic, tartaric, ascorbic and malic) measured by HPLC and evaluated for their antimicrobial activities against two species of Gram positive bacteria (S. aureus, B. cereus) and three species of Gram negative bacteria (E. coli, P. aeruginosa and Salmonella sp.) using disc diffusion and broth dilution method. Averrhoa bilimbi and Eleiodoxa conferta that shows high acid contents were tested on cotton fabric stained with lipstick and ink to evaluate their abilities as a stain remover. The results showed that titratable acidity content increased through maturity stages of fruits and conversely for total soluble solids content and pH value. Meanwhile, quantification of organic acid from selected fruits shows that oxalic acid and ascorbic acid were present at all stages of five local fruit types and ascorbic acid found has low concentrations. Tartaric acid was only present on Bouea oppositifolia while malic acid presents in all local fruit types except Mangifera indica. Oxalic acid was the predominant organic acids in Averrhoa bilimbi and Eleiodoxa conferta fruit.